2000
DOI: 10.1002/(sici)1097-4636(20000605)50:3<322::aid-jbm5>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Third-body wear of cobalt-chromium-molybdenum implant alloys initiated by bone and poly(methyl methacrylate) particles

Abstract: The potential for bone and poly(methyl methacrylate) (PMMA) debris to initiate wear on ASTM-F75 and ASTM-F799 CoCrMo alloys articulating against ultrahigh molecular weight polyethylene (UHMWPE) was investigated. Third-body wear particles of bone and PMMA bone cement (with and without the radiopacifier, barium sulfate) were introduced between CoCrMo and UHMWPE in a reciprocating sliding wear test. A scanning electron microscope and a white light interference surface profilometer were used to study the surface d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Multidirectional scratching of the femoral heads, similar to that in the present specimens, was observed. Que and Topoleski (2000) found that particles of polymerized bone cement (both with and without barium sulfate) or of bone, when added to the lubricant fluid, scratched CoCrMo specimens articulating in a pin-on-disc test against UHMWPE, with severe scratches on the metal being observed with as few as 2700 cycles. Davidson et al (1994) increased the wear of a UHMWPE pin articulating on CoCrMo by adding titanium particles to the lubricant fluid, with the amount of wear increasing with particle concentration, provided that a threshold concentration was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multidirectional scratching of the femoral heads, similar to that in the present specimens, was observed. Que and Topoleski (2000) found that particles of polymerized bone cement (both with and without barium sulfate) or of bone, when added to the lubricant fluid, scratched CoCrMo specimens articulating in a pin-on-disc test against UHMWPE, with severe scratches on the metal being observed with as few as 2700 cycles. Davidson et al (1994) increased the wear of a UHMWPE pin articulating on CoCrMo by adding titanium particles to the lubricant fluid, with the amount of wear increasing with particle concentration, provided that a threshold concentration was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Metallic debris predominates as third body particles, as demonstrated by a retrieval study of polyethylene liners involving quantification of embedded particles (Lundberg et al, 2007a); examples of metallic third body particles include porous ingrowth beads (Dowd et al, 2000;Najjar et al, 2000) or metal particles from the implants (Hirakawa et al, 2004;Huk et al, 1994;Kim et al, 2005;Lewis, 1997), from trochanteric reattachment fixation (Amstutz and Maki, 1978;Bronson, 1976;Hop et al, 1997), or from surgical instruments (Mackay et al, 2000). Third body particles can also originate from hydroxyapatite (Bauer et al, 1994;Bloebaum et al, 1997;Willie et al, 2000), bone (Que and Topoleski, 2000), or bone cement (Isaac et al, 1992;Joshi et al, 2001). Once they gain access to the space between the articulating components, third bodies can directly abrade both the acetabular and femoral head bearing surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbides are known to cause accelerated wear, as they become dislodged between the bearing surfaces causing third body wear. [35] Chromium oxide coatings on these alloys have been investigated to increase the wear resistance and due to its high hardness have shown lower wear rates compared to other coating materials currently used. [36] This produces less wear debris, reduces the amount of osteolysis occurring, and improves the life span of the implant.…”
Section: Effects Of Oxidesmentioning
confidence: 99%
“…From materials or combinations of materials used currently metal-on-UHMWPE (ultra high molecular weight polyethylene) bearings result in relative large volumetric wear [1][2][3], ceramics such as alumina [4][5][6] have an excellent wear resistance but are brittle, that may cause fracture during accidents, metal-on-metal bearings (usually CoCrMo alloys) [7][8][9] have good wear resistance, but release nanometric debris and ions that may cause allergy or have toxic effects. The desired alternative combination should posses the high fracture toughness of metals and the wear performance of ceramics.…”
Section: Introductionmentioning
confidence: 99%